Formulation and Evaluation of Torsemide Pellets for Extended Drug Release by Extrusion-spheronization Method - Karra, Narender (Asian Journal of Pharmaceutics (AJP), 2018)
Aim and Objective: The main objective of this study was to formulate extended release pellets of torsemide, a pyridineâ€“sulfonyl urea type loop diuretic. Materials and Methods: The preparations of torsemide pellets were prepared by extrusion-spheronization method. The prepared pellets were then coated with ethyl cellulose of different grades and Eudragit L30 D 55 and Eudragit NM 30 D grades at different concentrations as release retardant polymers using fluid bed processor, in this formulation hydroxypropyl methylcellulose used as a pore former and binder, microcrystalline cellulose PH101 as diluents and water used as a solvent. Results: The prepared pellets were evaluated for drug content, in vitro dissolution, differential scanning caloriemetry (DSC), Fourier transforms infrared (FTIR), and scanning electron microscopy (SEM). The drug release was extended up to 24 h and drug release was depended on polymer grade and polymer proportion. The optimized formulation showed 99 Â± 0.11 release in 24 h. The DSC and FTIR studies were showed the compatibility of the drug with a polymer, i.e., no drug-polymer interaction. Using SEM, it was shown that the torsemide pellets were porous and spherical in shape. Accelerated stability studies showed good similarity with the initial formulation indicated good stability for 6 months. In vivo, pharmacokinetic studies were conducted in rabbits by parallel design and pharmacokinetic parameters were calculated. Conclusion: By the above results, it can be concluded that the above-prepared pellets of torsemide could be able to extend the drug release by avoiding problems such as dose dumping, more gastric residence time, and improve the patient compliance. In vivo studies in rabbits were shown the increased half-life and bioavailability for a long duration.